Development of sintering processes and applications for 3D printing of electronics - Tan, Hong Wei (Nanyang Technological University, 2020)
3-dimensional (3D) printed electronics is one of the world’s fastest growing technologies in recent years. This new and upcoming technology has facilitated many innovative applications and high commercialisation of metallic nanoparticle inks. A robust and novel induction sintering technique is proposed to solve the major challenges faced by the current existing sintering techniques in sintering metallic nanoparticle inks. The induction sintering process is a non-contact selective sintering process, in which the electrically conductive pre-sintered printed patterns are only heated up by alternating electromagnetic field through eddy current losses. It is also more energy efficient and effective as compared to thermal sintering since the induction sintering process only heats the electrically conductive printed patterns rather than the entire substrate. The silver nanoparticles printed patterns after an induction sintering with thermal pre-sintering process achieved an average electrical resistivity of 1.98 × 10-8 Ω∙m, which is approximately 81% bulk conductivity of silver. However, this process still requires more than 1 hour of sintering time due to the time-consuming thermal pre-sintering process. In order to reduce the total sintering time required, the induction sintering technique was either coupled with infrared or intense pulse light sintering techniques. Thus, reducing the total sintering time to less than five minutes while still achieving excellent electrical conductivity. This new sintering technique also demonstrated its applicability to sinter different types of nanoparticle inks such as gold and platinum nanoparticle inks. This research hence has the potential to overcome the challenges faced in 3D printed electronics, in which printed patterns with high electrical conductivity can be printed on flexible substrates.